Biological Toxicity of Heavy Metal(loid)s in Natural Environments: From Microbes to Humans - Ding, Chunlian; Chen, Jianxin; Zhu, Feng; Chai, Liyuan; Lin, Zhang; Zhang, Kejing; Shi, Yan (Frontiers in Environmental Science, 2022)
Excessive levels of heavy metal(loid)s (HMs) in natural environments pose a serious threat to living beings worldwide. HM exposure causes irreversible damage to structural components and metabolic processes in living organisms, as has been observed in multiple studies on various organisms. In the natural environment, biological individuals interact with others through the food web rather than exist independently, which facilitates the transfer of HMs in the food web. However, the difference in HM toxicity among different biological species has not been elucidated. This review provides information on the speciation and migration of HMs in different environments to clarify the HM exposure routes of different biological species. The differences in the biotoxicity of HMs to different species, from microbes to humans, are emphasized. The relationship between HM toxicity and biological species is confirmed by the fact that HMs can be transferred and bioaccumulated along the food chain. Effective strategies for decreasing HMs emissions and removing HMs from the environment are briefly discussed. Finally, the limitations of the present study and future perspectives are discussed.